2020
DOI: 10.34119/bjhrv3n5-144
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre o nível de atividade física e a existência de comorbidades em policiais militares: Atividade física durante a pandemia do COVID-19 / Correlation between the level of physical activity and the existence of comorbities in military policies: Physical activity during the COVID-19 pandemic

Abstract: Correlação entre o nível de atividade física e a existência de comorbidades em policiais militares: Atividade física durante a pandemia do COVID-19 Correlation between the level of physical activity and the existence of comorbities in military policies: Physical activity during the COVID-19 pandemic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
5
1
2
Order By: Relevance
“…The causes of absence from service due to physical and mental health problems among the military police were around 29 days of absence. These data are superior to the studies by Oliveira [22] who identified that (21.02%) of the analyzed police officers were away at least 1 day from work in the last year, that is, much lower than the studies in Rondônia. These questions point out how important social, demographic and labor factors are in maintaining health and quality of life [48].…”
Section: Level Of Physical Activity and Health Conditions Of Military...contrasting
confidence: 90%
See 4 more Smart Citations
“…The causes of absence from service due to physical and mental health problems among the military police were around 29 days of absence. These data are superior to the studies by Oliveira [22] who identified that (21.02%) of the analyzed police officers were away at least 1 day from work in the last year, that is, much lower than the studies in Rondônia. These questions point out how important social, demographic and labor factors are in maintaining health and quality of life [48].…”
Section: Level Of Physical Activity and Health Conditions Of Military...contrasting
confidence: 90%
“…On the other hand, Covid-19 also generates psychological problems and stressors inside the barracks and among the police. Therefore, it is "essential for the Police to review their physical activity programs, as well as to keep their active duty soldiers in good health, whether in times of normality or in times of a pandemic" [22].…”
Section: Level Of Physical Activity and Health Conditions Of Military...mentioning
confidence: 99%
See 3 more Smart Citations